Exploring Ubuntu-Based Research Methodologies in Southern African Bantu People's Embodied Movements: Ethical Considerations, Community-Based Strategies, and Philosophy - Alois Maluleke (Conversations Across the Field of Dance Studies)
This paper investigates the complex overlap between Ubuntu research methodologies, the bodily expressions of Southern African Bantu communities, and the philosophical foundations of dance in comprehending cultural diversity. Drawing from ethnographic fieldwork in the Gwembe Valley Tonga community in Zambia in 2022, the author highlights the importance of Ubuntu research methodologies in encouraging cross-cultural understanding and mutual respect. The paper underscores how embodied movements within Bantu cultures capture identity, tradition, and community organisation beyond mere performance. It explores the historical and cultural context of Bantu people's embodied movements, connecting them to Ubuntu principles of interconnectedness and communal welfare. The paper discusses ethical considerations like cultural sensitivity and informed consent, along with community-based strategies rooted in Ubuntu philosophy for fostering individual and collective well-being.